Growth, Inequality, and Poverty: An Analysis of Pro-Poor Growth in Indonesia - Permadi, Yudistira Andi (Jurnal Ekonomi Kuantitatif Terapan; 2018: Vol. 11, No. 2, Agustus 2018 (pp. 147-253)DO - 10.24843/JEKT.2018.v11.i02.p08, 2018)
In the concept of pro-poor growth, economic growth accompanied by fair income distribution will accelerate the rate of poverty reduction. By employing extensive data of household expenditures and other economic indicators, the study will examine the performance of economic growth in Indonesia whether it has been pro-poor over the period 2005-2013. We employ two methods in this article, Growth Incidence Curve (GIC) method, and Pro-Poor Growth Index (PPGI) method. By applying the GIC method, our empirical results indicate that economic growth in Indonesia has not been pro-poor during the observed period. The curve shows that the highest income population enjoys increased consumption more than the poorest population. Furthermore, PPGI method has revealed that economic growth, inequality, and an interaction term between economic growth and inequality have been significant to influence poverty incidence in Indonesia. Our empirical result also reveals that among manufacturing, agriculture, and services sector; it was manufacturing that has successfully reduced the number of the poor, while agriculture unexpectedly had a devastating impact on the number of poor people. The services sector, meanwhile, had not contributed to poverty alleviation. Furthermore, none of the government spending in education and health that significantly contributes to poverty alleviation.